2021
DOI: 10.1172/jci.insight.150551
|View full text |Cite
|
Sign up to set email alerts
|

Propensity of IgA to self-aggregate via tailpiece cysteine-471 and treatment of IgA nephropathy using cysteamine

Abstract: IgA nephropathy is caused by deposition of circulatory IgA1 in the kidney. Hypo-galactosylated IgA1 has the propensity to form poly-IgA aggregates that are prone to deposition. We purified poly-IgA from the plasma of IgAN patients and showed the complex being susceptible to reducing condition, suggesting intermolecular disulfide connections between IgA units. We sought to find the cysteine residue(s) in forming intermolecular disulfide. Naturally assembled dimeric IgA, also known as secretory IgA, involves a J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This was validated by chromatography, where there was a predominance of d IgA2 over m IgA2 upon JC coexpression, as compared to m IgA2 or aggregates of IgA2 that assembled in the absence of the JC ( Fig. 1C ) ( 22 ). Notably, size exclusion chromatography retention times of the d IgA2 and m IgA2 peaks were nearly identical between IgA2 mRNA and IgA2 R ( Fig.…”
Section: Resultsmentioning
confidence: 69%
“…This was validated by chromatography, where there was a predominance of d IgA2 over m IgA2 upon JC coexpression, as compared to m IgA2 or aggregates of IgA2 that assembled in the absence of the JC ( Fig. 1C ) ( 22 ). Notably, size exclusion chromatography retention times of the d IgA2 and m IgA2 peaks were nearly identical between IgA2 mRNA and IgA2 R ( Fig.…”
Section: Resultsmentioning
confidence: 69%
“…The absence of the N-glycan in the tailpiece is known to cause the formation of larger oligomers (Xie et al, 2021;Pan et al, 2024). Lombana et al (2019) previously observed this phenomenon during dimeric IgA2 (m2) production when coexpressing heavy chain (HC), light chain (LC), and the joining chain (JC).…”
Section: Production Of Different Iga2 (M2) Glycosylation Variantsmentioning
confidence: 99%
“…In addition, there is a conserved tail structure consisting of 18 amino acids at the C-terminal of the CH3 region on the IgA heavy chain. This kind of tail is essential for the formation of divalent and multivalent structures of IgA ( Xie et al, 2021 ).…”
Section: Structure Function and Classification Of Immunoglobulin Amentioning
confidence: 99%
“…Half of the glycans found at this site are core-fucosylated ( Huang et al, 2015 ). The N -glycans at this site are required for the correct conformation of J chain, deletion of them can prevent the dimeric IgA formation and inhibit the pIgR-mediated epithelial transport of IgA ( Xie et al, 2021 ).…”
Section: Structure Of Immunoglobulin a Glycosylationmentioning
confidence: 99%